2008
DOI: 10.1590/s0066-782x2008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Custo-efetividade da trombólise pré-hospitalar vs intra-hospitalar no infarto agudo do miocárdio

Abstract: SummaryBackground: There is evidence that prehospital thrombolysis improves the outcome in ST-elevation myocardial infarction (STEMI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…When available, prehospital thrombolysis was shown to reduce costs in Brazil. 65 The use of electrocardiogram machines for patient triage in primary health centres was shown to be cost-effective in India at $12 per QALY gained. 51 The use of aspirin and β blockers was shown to cost about $10–20 per DALY averted, streptokinase about $700 per QALY gained, and more fibrin-specific thrombolytics (such as tissue plasminogen activator) about $15 000 per QALY.…”
Section: Cost-effectiveness Of Interventions For Cvrdsmentioning
confidence: 99%
“…When available, prehospital thrombolysis was shown to reduce costs in Brazil. 65 The use of electrocardiogram machines for patient triage in primary health centres was shown to be cost-effective in India at $12 per QALY gained. 51 The use of aspirin and β blockers was shown to cost about $10–20 per DALY averted, streptokinase about $700 per QALY gained, and more fibrin-specific thrombolytics (such as tissue plasminogen activator) about $15 000 per QALY.…”
Section: Cost-effectiveness Of Interventions For Cvrdsmentioning
confidence: 99%
“…Tissue plasminogen activator was found to be cost-effective, when used within 6 h of ischemic stroke [ 56 ] and when compared to Streptokinase [ 57 ]. In one study, prehospital thrombolysis was found to be cost-effective compared to in-hospital use [ 58 ]. Streptokinase was moderately cost-effective when used in combination with other BP medication [ 18 , 51 ], but not cost-effective when used alone [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…There was only one cost–benefit analysis [ 27 ]. Overall, among the 20 studies which did CEA, life years gained/saved was the predominant benefit measure [ 23 25 , 41 , 44 , 45 , 49 , 50 , 52 , 57 , 58 , 62 , 63 ], while the rest of the studies either used drop in blood pressure [ 33 , 34 , 37 , 39 ], avoided CVD [ 24 , 44 , 61 ] or restenosis [ 60 ] event as benefit measure. Out of 38 studies that mentioned their approach to defining an intervention as cost-effective or not, 7 employed the willingness to pay threshold, while the majority (n = 31) used the WHO’s Commission on Macroeconomics and Health (CMH) threshold using the respective countries’ GDP per capita.…”
Section: Resultsmentioning
confidence: 99%
“…Our study has several limitations. First, the study was performed based on a decision-analytic Markov model which was a simplification of reality, where probability data of outcomes occurred in another population and different scenarios from that of 5C trial were inevitably employed, although we used a resource estimate adapted to our reality [ 23 ]. The data sources about probabilities beyond 1 year were partly driven by the clinical event rates observed in the patients with NSTE-ACS or STEMI patients, while the population in 5C trial were combined NSTE-ACS patients and STEMI patients together.…”
Section: Discussionmentioning
confidence: 99%